Klasyfikacja ryzyka niewypłacalności klientów w telekomunikacji - Ząbkowski, Tomasz; Szczęsny, Wiesław (Customer Insolvency Classification in the Telecommunication Market, 2009)
The article presents an application of classification methods (decision trees and decision trees with boosting) for customer insolvency problem on the example of the telecommunication market. Based on characteristics of the customers, models to estimate their credit risk were proposed. Five groups of the customers were proposed based on employment status. The results confirm the usefulness and high performance of the methods proposed. The approach to analyze customers in groups can be considered as a good method for more effective revenue assurance. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 123-131